2017
DOI: 10.24263/2225-2924-2017-23-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Optical Images of Vegetable Assemblies

Abstract: In the article it is shown that for the operative estimation and analysis of optical images of objects of plants using spectral characteristics in the optical range, data have considerable volumes. The data is represented by an additive color model in RGB format, which requires significant numerable resources for their use in neural networks. It is proposed instead of a large sample size on the input of the neural network to provide statistical characteristics of the sample, which reduces the numerable resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As can be seen Note that composition of the areas on the micrographs marked with respective geometric symbols is given in Table 1. [41] reported as a source for PDF (ICDD, 2008) record [44], a for Hf-containing D8 a phase is equal to 11.480 Å. In the alloy with x = 8 investigated in the current study it is higher by 5 · 10 −2 Å.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…As can be seen Note that composition of the areas on the micrographs marked with respective geometric symbols is given in Table 1. [41] reported as a source for PDF (ICDD, 2008) record [44], a for Hf-containing D8 a phase is equal to 11.480 Å. In the alloy with x = 8 investigated in the current study it is higher by 5 · 10 −2 Å.…”
Section: Resultsmentioning
confidence: 94%
“…There is only a limited information in the literature regarding the fcc-Fe 16 Hf 6 Si 7 D8 a -type phase isostructural with Mg 16 Cu 6 Si 7 [39]. To the best of our knowledge, the phase with the exact composition was described only two times, by Lisenko et al [40] and Lisenko [41]. Rixecker and Haberkorn [39] found that D8 a and C14 phases can coexist in annealed Fe 16 Ta 6 Si 7 and Fe 16 Nb 6 Si 7 amorphous powders obtained by mechanical alloying what complies with the findings stated in the present study.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation